Polski Atlas Etnograficzny — wyzwania wobec współczesności - Diakowska-Kohut, Edyta (Studia Etnologiczne i Antropologiczne, 2012)
The article presents an over 65-year history and output of the Polish Ethnographic Atlas, treated as an invaluable source of information on the Polish traditional culture. The main challenge to be currently faced by the Atlas Studio, is actions in favour of the maintenance and promotion of cultural heritage included in the materials from the field studies. The very materials prove the elements of cultural heritage comprising information on disappearing beliefs, traditions, ceremonies, social and economic behaviours such as agriculture, farming, rural construction, or traditional craft. Thus, what becomes necessity is digitalization allowing for maintaining and popularizing Atlas. Making digital copies and their availability is extremely important for maintaining cultural heritage for future generations. On the other hand, it will protect this part of the output of Polish ethnology, namely a valuable and unique collection of the materials of the Polish Ethnographic Atlas.